2012
DOI: 10.1063/1.3674986
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics and residual strain in metamorphic AlSb on GaAs

Abstract: We have observed the evolution of the accumulated stress during heteroepitaxial growth of highly lattice mismatched AlSb on GaAs by measuring the deformation of the substrate as a function of time. High resolution transmission electron microscopy images show almost all of the plastic relaxation is accommodated by an array of 90° misfit dislocations at the interface. The in-plane lattice parameter of the resulting metamorphic AlSb is slightly smaller (0.3%) than the bulk value and perfectly matches the lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…Both thin and thick AlSb layers grown using low-temperature (LT) technology were taken under consideration. The thinnest layers had thicknesses comparable to the critical value determined from Matthews-Blakesly formula under the assumption of 2D growth modes [22], whereas the thickest to the multiple of the island coalescence limit determined by Ripalda et al [23]. The results proved the role of both LT-AlSb layers in the process of TDD reduction.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Both thin and thick AlSb layers grown using low-temperature (LT) technology were taken under consideration. The thinnest layers had thicknesses comparable to the critical value determined from Matthews-Blakesly formula under the assumption of 2D growth modes [22], whereas the thickest to the multiple of the island coalescence limit determined by Ripalda et al [23]. The results proved the role of both LT-AlSb layers in the process of TDD reduction.…”
Section: Introductionsupporting
confidence: 65%
“…Strong reduction of dislocation density was observed, especially if EPD values were to be considered (2.2 × 10 6 cm −2 ). The thickest AlSb layer worsened the crystal quality of GaSb material (#648) in comparison with the previously analyzed sample #651, even though, it was significantly thinner than the limit of the accumulation of own compressive strain determined by Ripalda et al [23] (42.0 nm). Nevertheless, the filtering role of AlSb was maintained.…”
Section: The Investigations With Lt-alsb Layercontrasting
confidence: 52%
See 1 more Smart Citation
“…The RHEED and AFM analysis of the early stages of AlSb growth on Si indicate that AlSb epilayers also form islands on Si or GaAs substrates, [7][8][9][10][11] which are denser and coalesce at significantly lower thicknesses as compared to GaSb. 12 It has also been observed that introducing a thin buffer layer of AlSb can significantly improve the quality of GaSb films by accelerating the plateau-like growth of GaSb among AlSb islands.…”
Section: Introductionmentioning
confidence: 99%
“…And threading dislocations in the InAs metamorphic buffer can penetrate into the active region and act as traps inducing leakage current and/or trap-assist tunneling. The threading dislocation can be reduced by using an AlSb or GaSb metamorphic buffer, since 90 o dislocations instead of 60 o dislocations are likely formed at the antimonide/GaAs interface that would not penetrate into the active region [3]. Then the InAs layer has to be replaced by InAs x Sb 1-x since the active layer has to be lattice matched to the metamorphic buffer.…”
mentioning
confidence: 99%